2015
DOI: 10.2174/1874325001509010412
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality Amongst Patients Sustaining Neck of Femur Fractures as In-Patients in a Trauma Centre

Abstract: Purpose: Neck of Femur (NOF) fracture is a common injury with high mortality that all orthopaedic departments must contend with [1]. The aim of this study was to report incidence and mortality of NOF fractures occurring while patients were being admitted to hospital for other conditions.Methods: A retrospective review was performed of all NOF fracture admissions between 1st of Jan 2010 to 31st of Dec 2012 at a University Hospital trauma centre. Fractures were divided according to the location where the fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“… 14 Inpatient hip fractures have higher mortality when compared to those from the community. 15 After adjustment for age and gender, the odds of inpatient mortality was 2.25 times higher for inpatient hip fracture and the odds ratio was raised for both 90-day and one-year mortality. 15 IF in single rooms has been associated with a significantly higher incidence of hip fracture in a hospital design with single rooms as compared with a multi-bedded facility.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 14 Inpatient hip fractures have higher mortality when compared to those from the community. 15 After adjustment for age and gender, the odds of inpatient mortality was 2.25 times higher for inpatient hip fracture and the odds ratio was raised for both 90-day and one-year mortality. 15 IF in single rooms has been associated with a significantly higher incidence of hip fracture in a hospital design with single rooms as compared with a multi-bedded facility.…”
Section: Introductionmentioning
confidence: 95%
“… 15 After adjustment for age and gender, the odds of inpatient mortality was 2.25 times higher for inpatient hip fracture and the odds ratio was raised for both 90-day and one-year mortality. 15 IF in single rooms has been associated with a significantly higher incidence of hip fracture in a hospital design with single rooms as compared with a multi-bedded facility. 16 In multivariate analyses, IF had been independently correlated with significantly higher length of stay (LoS) and substantially increased utilization of resources following injurious falls.…”
Section: Introductionmentioning
confidence: 95%
“…Green et al concluded that 78% of inpatient proximal femoral fractures occur on acute medical and rehabilitation wards[ 12 ]. Mohamed et al displayed that 48% of inpatient falls occurred on medical wards and 38% of falls occurred on geriatric/elderly medicine rehabilitation wards[ 13 ]. These findings were consistent with the results of this study, which found that 54% of patients sustaining proximal femoral fractures as inpatients were located on medical wards, at the time of their injury and 35% were on rehabilitation wards.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Hip Fracture Database (NHFD), 2,511 (3.9% of all hip fractures) patients in 2015 and 2,659 patients (4.1%) in 2016 were treated for an inpatient fracture, meaning that this is an increasing problem [4, 5]. Other research performed in individual hospital trusts report that approximately 5.5 - 6.1% of hip fractures occur following a fall within a hospital environment [6-8]. Although the higher incidence of fracture in these studies can be explained by characteristics of the trusts (as two units included injuries from rehabilitation centres within their trusts), another reason may be the reliability of NHFD data.…”
Section: Introductionmentioning
confidence: 99%
“…There is no guidance as to whether the time of fall or the time at which the injury is diagnosed should be when the clock is started in order to ensure prompt treatment, nor are there agreed protocols for the immediate post-falls care of these patients or incident reporting [12]. This is important as such patients have been shown to have a higher level of impaired mental status, co-morbidity (including respiratory, renal, endocrine and malignant pathologies) [7, 13], and risk of postoperative mortality of 35.7 - 50% within 1 year compared to 21.5 – 31.2% those falling in the community [6-8]. Compensation has also been paid to patients following an inpatient fall resulting in FNOF [14, 15] hence this is becoming increasingly important from a medicolegal perspective.…”
Section: Introductionmentioning
confidence: 99%